(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The development of popcorn genotypes that are high-yielding and with high popping abilities is fundamental to the expansion of popcorn production. In this study, a total of 23 newly developed full-sib FS3 lines of popcorn were evaluated under upland field conditions in the spring cropping season in 2021. The plant genotypes were evaluated for growth duration, plant height, number of leaves, ears/plant, ear length, ear diameter; the number of kernels, seeds per row, 1000-seeds weight, seed yield, and the proportion of floury endosperm, and popping indicator. Our results showed that the growth duration of the popcorn lines ranged from 96 - 121 days, plants were between 103.7 - 200.6 cm in height, and the number of leaves ranged between 12.92-18.13. The number of ears/plant, ear length, ear diameter, and number of kernel rows and seeds per row were 0.3-1.3, 9.6 - 20 cm, 2.3 - 4.2 cm, 7.33 -13.6 and 6.2 - 31.9, respectively. The popcorn lines were diverse in grain color and classified into white, yellow, black, pink, white yellow, and white pink. The grain yield varied from 2.13 - 64.58 quintals/ha, in which NO-11 had the highest yield of 64.58 quintals/ha. Popping indicators varied among genotypes and were negatively and positively correlated with 1000-seed weight and proportion of floury endosperm, respectively. In this study, we identified some genetic resources, such as NO-2, NO-12, NO-14, NO-20, and NO-22, which had the best popping ability. These resources will provide insights into the mechanisms of popping ability and important materials for breeding programs. J Bangladesh Agril Univ 22(3): 285-294, 2024